2022
DOI: 10.3390/foods11203185
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Process, Structure Characterization, and Antioxidant Activity of Polysaccharides from Different Parts of Camellia oleifera Abel

Abstract: The flowers, leaves, seed cakes and fruit shells of Camellia oleifera are rich in bioactive polysaccharides, which can be used as additives in food and other industries. In this study, a Box−Behnken design was used to optimize the extraction conditions of polysaccharides from C. oleifera flowers (P-CF), leaves (P-CL), seed cakes (P-CC), and fruit shells (P-CS). Under the optimized extraction conditions, the polysaccharide yields of the four polysaccharides were 9.32% ± 0.11 (P-CF), 7.57% ± 0.11 (P-CL), 8.69% ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…While kaempferol glycosides constitute the primary component of TFCO at 98.44%, the potential influence of other active ingredients on the experimental outcomes should not be overlooked. The bioactive compounds in C. oleifera defatted seeds predominantly include flavonoids [17][18][19][20][21], saponins [22,23], and polysaccharides [24,25]. Notably, saponins obtained from C. oleifera possessed in vivo anti-inflammatory activity [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While kaempferol glycosides constitute the primary component of TFCO at 98.44%, the potential influence of other active ingredients on the experimental outcomes should not be overlooked. The bioactive compounds in C. oleifera defatted seeds predominantly include flavonoids [17][18][19][20][21], saponins [22,23], and polysaccharides [24,25]. Notably, saponins obtained from C. oleifera possessed in vivo anti-inflammatory activity [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its industrial utility, contemporary research has ventured into tapping its therapeutic potential. The residual defatted seed pomace of C. oleifera is rich in bioactive substances, predominantly flavonoids [17][18][19][20][21], saponins [22,23], and polysaccharides [24,25]. Among these, flavonoids, principally kaempferol glycosides, manifest a broad spectrum of biological activities, encompassing anti-inflammation [20,21,26], anti-oxidation [26,27], anti-melanogenesis [27], and anti-microbial [28] activities.…”
Section: Introductionmentioning
confidence: 99%
“…The response surface reflects the effect of the interaction between the two variables on the SDF yield, keeping the others constant at the central levels [39]. As seen in Figure 2, the response value first increased and then decreased with each factor level increasing.…”
Section: Response Surface Interaction Analysismentioning
confidence: 96%
“…As a traditional Chinese medicine, C. oleifera bud has the effect of blood cooling and hemostasis and is utilized to treat vomiting blood, hematochezia, and scald ( Chinese Materia Medica Editorial Committee, 1999 ; Sugimoto et al, 2009 ). Past studies have revealed that C. oleifera flower bud contains polysaccharides, phenolics, flavonoids, and procyanidins as well as possesses antioxidant and gastroprotective effects ( Feng et al, 2022 ; Xiang et al, 2022 ; Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%